The multi-point assessment of the kinematics of shocks (MAKOS) - Goodrich, Katherine; Cohen, Ian J.; Schwartz, Steven; Wilson, Lynn B.; Turner, Drew; Caspi, Amir; Smith, Keith; Rose, Randall; Whittlesey, Phyllis; Plaschke, Ferdinand (Frontiers in Astronomy and Space Sciences, 2023)
Collisionless shock waves are one of the main mechanisms of energy conversion in space plasmas. They can directly or indirectly drive other universal plasma processes such as magnetic reconnection, turbulence, particle acceleration and wave phenomena. Collisionless shocks employ a myriad of kinetic plasma mechanisms to convert the kinetic energy of supersonic flows in space to other forms of energy (e.g., thermal plasma, energetic particles, or electromagnetic energy) in order for the flow to pass an immovable obstacle. The partitioning of energy downstream of collisionless shocks is not well understood, nor are the processes which perform energy conversion. While we, as the heliophysics community, have collected an abundance of observations of the terrestrial bow shock, instrument and mission-level limitations have made it impossible to quantify this partition, to establish the physics within the shock layer responsible for it, and to understand its dependence on upstream conditions. This paper stresses the need for the first ever spacecraft mission specifically designed and dedicated to the observation of both the terrestrial bow shock as well as Interplanetary shocks in the solar wind. Our mission concept, the Multi-point Assessment of the Kinematics of Shocks (MAKOS), will greatly improve on previous observations of the terrestrial bow shock with instrumentation specifically tailored to observe the evolution of the solar wind through the shock.Understanding collisionless shocks is vital to the understanding of our universe, from the heating and deflection of bulk flows to the acceleration of cosmic rays. Moreover, collisionless shocks directly influence our own terrestrial space environment, e.g., solar windmagnetosphere interactions.Vital questions regarding collisionless shocks remain unanswered:1. What is the partition of energy across collisionless shocks?2. What are the processes governing energy conversion at and within collisionless shocks?3. How and why do these processes vary with macroscopic shock parameters?In this paper, we will discuss why addressing these questions is of critical importance. The path forward to make significant progress towards addressing these questions is through the implementation of MAKOS (Multi-point Assessment of the Kinematics of Shocks) an STP class mission consisting of four satellites with a full particle and fields instrument suite.